Effect of obstructive sleep apnea on right ventricular ejection fraction in patients with hypertrophic obstructive cardiomyopathy. Issue 10 (16th September 2020) - Wang, Shengwei; Cui, Hao; Ji, Keshan; Ren, Changwei; Guo, Hongchang; Zhu, Changsheng; Lai, Yongqiang; Wang, Shuiyun
Abstract: Background: Obstructive sleep apnea (OSA) is a common disease associated with worse structural and functional impairment of the heart in patients with hypertrophic obstructive cardiomyopathy (HOCM). Hypothesis: The presence and severity of OSA can decrease the right ventricular ejection fraction (RVEF) in patients with HOCM. Methods: In total, 151 consecutive patients with a confirmed diagnosis of HOCM at Fuwai Hospital between September 2017 and September 2018 were included. Polysomnography and cardiac magnetic resonance imaging were performed in all patients. Results: Overall, 84 (55.6%) patients were diagnosed with OSA. The RVEF significantly decreased with the severity of OSA (none, mild, moderate‐severe: 46.1 ± 8.2 vs 42.9 ± 7.5 vs 41.4 ± 7.4, P = .009). The apnea‐hypopnea index (AHI) was significantly high in patients with RVEF<40% among the different OSA groups (mild, moderate:7.7 ± 2.4 vs 9.6 ± 2.9, P = .03; 24.4 ± 9.0 vs 36.3 ± 18.0, P = .01). In the multiple linear regression model, the right ventricular end‐systolic volume (β = −0.28, P  < .001), AHI (β = −0.09, P = .02), and oxygen desaturation index (β = −0.11, P = .04) were independently associated with a decrease in RVEF (adjusted R 2 = 0.347, P  < .001). Furthermore, the prevalence of RVEF<40% was high in patients with OSA. Compared with RVEF>40%, RVEF<40% was associated with more symptoms, mainly chest pain, chest distress, NYHA class III or IV, pulmonary hypertension, and moderate or severe mitral regurgitation. Conclusion: In patients with HOCM, the presence and severity of OSA is independently associated with a lower RVEF. In addition, compared with patients with RVEF>40%, those with RVEF<40% had more symptoms, including chest pain, chest distress, and NYHA class III or IV.